2015
DOI: 10.1177/2325967115s00133
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Effect of Capsular Shift in the Treatment of Hip Microinstability. Creation and Testing of a Novel Hip Instability Model

Abstract: Objectives:The objective of the study was to create a cadaveric model of hip capsule laxity and evaluate the biomechanical effects of a capsular shift used to treat hip instability on this model.Methods:Eight fresh frozen cadaveric hips, average age 58.5, were tested with a custom hip jig. To create the hip laxity model, the capsule was stretched in extension under 35Nm of torque for 1 hour in neutral rotation. Specimens went through a series of six testing conditions: intact, vented, stretched, capsulotomy, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(60 citation statements)
references
References 14 publications
3
57
0
Order By: Relevance
“…6,7 Some authors have attributed postoperative instability to the violation of the capsule during the operation. 8,9 The fibrous hip joint capsule is a confluence of 4 ligaments (the iliofemoral, pubofemoral, and ischiofemoral ligaments and the zona orbicularis) that provides static Repaired or unrepaired capsulotomy after hip arthroscopy: a systematic review and meta-analysis of comparative studies constraint to the joint and is believed to be an important stabiliser of the hip joint. 10,11 During hip arthroscopy, a capsulotomy is necessary for visualisation and operation.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Some authors have attributed postoperative instability to the violation of the capsule during the operation. 8,9 The fibrous hip joint capsule is a confluence of 4 ligaments (the iliofemoral, pubofemoral, and ischiofemoral ligaments and the zona orbicularis) that provides static Repaired or unrepaired capsulotomy after hip arthroscopy: a systematic review and meta-analysis of comparative studies constraint to the joint and is believed to be an important stabiliser of the hip joint. 10,11 During hip arthroscopy, a capsulotomy is necessary for visualisation and operation.…”
Section: Introductionmentioning
confidence: 99%
“…(For a detailed summary for each study's scope, methods, and observations, see Appendix Table I. ) in extension under 35 Nm of torque for 1 hour) and suggested that side-to-side repair only partially decreased distraction resistance, while a capsular shift approach restored joint stability 11 . Although capsular plication may help to restore joint stability in extreme cases of joint subluxation, it perhaps should not be a routine procedure for all capsular closures.…”
Section: Surgical Management Hip Preservation Capsulotomy and Repairmentioning
confidence: 99%
“…It is essential to understand that capsular characteristics and mechanical properties of the hip with pathological conditions are different (i.e., a thicker, stiffer capsule) than a healthy joint 38,50,52 ; thus, the need for full capsular closure may depend on several other confounding factors (e.g., age, sex, osseous anatomy, and muscle function) [53][54][55] . More importantly, since unrepaired capsulotomies have been shown to heal within 24 weeks postoperatively 56 , and completely resecting the iliofemoral ligament does not destabilize the native hip 43 , there is evidence that not all capsulotomies need to be repaired after The findings of in vitro cadaveric studies on the effects of capsular conditions and surgical stages, outlining the contributions of the interportal capsulotomy 5,7,8,10,11,14,46 and T-capsulotomy 6,11,14,15,46 and the effects of instability 7,[11][12][13]16,47 , effusion arthroscopy, especially when capsular contracture may be part of the pathological process. It is still unclear what leads to inherent or iatrogenic instability; thus, if the native head size is not substantially reduced or altered, capsular repair in the setting of a small arthroscopic capsulotomy may not be necessary in the otherwise congruent and stable hip 4,54,56 .…”
Section: Surgical Management Hip Preservation Capsulotomy and Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…When considering kinematic alterations to the hip joint, unrepaired interportal capsulotomy increases external rotation and decreases the force required for distraction as compared with the native hip. 15,[19][20][21] While interportal capsulotomy facilitates adequate visualization and access for diagnostic and interventional purposes, size of incision has been reported to correlate with the degree of iatrogenic instability. The length interportal capsulotomy may vary as small as 2 cm to greater than 6 cm depending on the pathology as well as surgeon preference.…”
Section: Surgical Management Of the Capsulementioning
confidence: 99%